1992
DOI: 10.1177/104063879200400121
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofLeptospira InterrogansSerovarsBratislavaandHardjofrom Swine at Slaughter

Abstract: Brief communications 87A and B were added to each cupule, and the reactions were allowed to develop for 5 minutes at room temperature. The color intensity of the reactions was compared to the manufacturer's scheme and graded as follows: 0, no color change; trace, ≤ 5 nanomoles (nmol); 1, 5 nmol; 2, 10 nmol; 3, 20 nmol; 4, 30 nmol; and 5, ≥40 nmol. Both grade 0 and trace reactions, which produced only slight color changes, were scored as negative reactions; grade 1, as weak positive reactions; and grades 2-5 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…Based on the high titres indicating active infection, and the high frequency of seropositive animals for Bratislava and Pomona serovars, humans that come into contact with feral swine are most likely to be exposed to these serovars. It is not surprising that these serovars were commonly identified in the feral swine we tested because they have been reported previously in both domestic swine [6,8] and feral swine [15,16]. Serovars Pomona and Bratislava have also been commonly identified in feral swine not only in the United States [11][12][13]30], but also in countries around the world such as Spain [14], Italy [31], Australia [15,32], Japan [24], and Germany [16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the high titres indicating active infection, and the high frequency of seropositive animals for Bratislava and Pomona serovars, humans that come into contact with feral swine are most likely to be exposed to these serovars. It is not surprising that these serovars were commonly identified in the feral swine we tested because they have been reported previously in both domestic swine [6,8] and feral swine [15,16]. Serovars Pomona and Bratislava have also been commonly identified in feral swine not only in the United States [11][12][13]30], but also in countries around the world such as Spain [14], Italy [31], Australia [15,32], Japan [24], and Germany [16].…”
Section: Discussionmentioning
confidence: 98%
“…Pigs have been identified as reservoir hosts for the disease in humans [6], which is significant since pigs have similar anatomy, genetics and physiology to humans [7], and could serve as a source of infection to those with the potential for occupational exposure. The most common serovars infecting domestic swine in the United States are Bratislava, Grippotyphosa, and Pomona, with occasional reports of Canicola and Icterohaemorrhagiae [8]. Infection in pigs rarely causes death and is generally characterized by abortion, weakness, inability to stand, muscle spasms, and muscle rigidity [4].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of bratislava is not known, 6 but strains of this serovar have been recovered from dogs 14 and pig 1,8 in the United States and from horses in Northern Ireland. [5][6][7] A high prevalence of antibodies against bratislava and the isolation of bratislava from the kidney of 7 of 91 adult horses indicated that horses may be the maintenance host for serovar bratislava in Northern Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…Serovar kennewicki was recovered from 5 of these 8 cases, suggesting that these mares were previously exposed to bratislava and that infection by serovar kennewicki stimulated titers against bratislava or that the mares were infected with both serovars. Serovar bratislava is extremely fastidious 1,8 and would probably not grow in the medium used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many pathogens, both viral and bacterial, were initially implicated, by virtue of their isolation from many clinical cases, yet no pathogen was able to reproduce the disease experimentally, neither alone nor in combination [2,9,12,14,16,22,34,38,46,54,62]. The lack of consistent isolation of any single agent from cases of the disease however, suggested that, rather than being the primary agents, their presence was opportunistic, causing secondary infections leading to multifactorial disease.…”
Section: Field Observations Of Immunomodulationmentioning
confidence: 99%